"Perilous movement" : deconstruction and the discourse of conflict - Ryan, Jennifer (Trinity College (Dublin, Ireland). School of English, 2003)
This thesis examines the relationship between the discourses of the university and the public press through an analysis of the work and career of Jacques Derrida. The conflictual nature of the reception of deconstruction, both in the public press and in the academy, has had an acute effect on Derrida to the extent that much of his work is by way of response to what he sees as misreadings of his thought.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin